The Effect of Good Corporate Governance and Capital Structure on Firm Value with Financial Performance as an Intervening Variable - Agus Ismaya Hasanudin; Bustanul Arifin; Satya Datara (International Journal of Integrative Sciences, 2023)
This research aims to examine the direct and indirect of good corporate governance and capital structure on firm value with financial performance as an intervening variable. The independent variables are Good Corporate Governance (GCG) measured by the composite self-assessment value and capital structure measured by the Debt to Equity Ratio (DER). The dependent variable in this research is firm value measured by Price to Book Value (PBV). The intervene variable in this research is financial performance measured by Return on Assets (ROA). The population in this research are banking companies listed on the Indonesian Stock Exchange 2017-2021 period. The results of this research that firm value can be influenced by GCG and capital structure positively and significantly, financial performance can be influence by GCG positively and significantly, but capital structure does not, firm value can be influence by financial performance positively and significantly, financial performance is able to intervene between GCG and firm value, and financial performance is not able to intervene between capital structure and firm value